Ceria - zirconia thin films : influence of nanostructure and moisture on charge transport properties - Kleine-Boymann, Matthias; Justus Liebig University Giessen (My University, 2021)
In the last decade a huge expansion of nano material applications being introduced into all kinds of markets is observed leading to a growing tendency to tailor the fabrication of materials with nano dimensions in order to tune their properties, optimizing them for a certain process. The same holds true for ceria based solid solutions. CeO2 - ZrO2 solid solutions are well established for the use as part of three-way catalytic converters in the exhaust gas cleaning system of combustion engines. Apart from that ceria is studied for the use in a wide range of applications, like solid oxide fuel cells, polymer exchange membrane fuel cells, both being almost fully developed to be introduced for a wide market. Next to others, currently emerging applications are the use of ceria as a catalyst for reforming processes, water-gas shift reaction or thermochemical water splitting. Due to the complexity of CeO2 - ZrO2- based materials the preparation of model systems has proven to be a highly versatile approach in order to gain a deeper understanding of specific phenomena. The same approach was used in the work presented here, following several preliminary studies on single crystalline material on the oxygen transport properties of ceria- zirconia solid solutions by means of surface analytical techniques and electrochemical impedance spectroscopy in the work group of Prof. Jürgen Janek. Thin films offer a more straightforward application of surface analysis techniques, as well as the possibility to tune the structural and electronic properties of the material under investigation. In this work CeO2 - ZrO2 thin films were deposited by means of pulsed laser deposition. The resulting Ce_{1-x}Zr_{x}O_{2} thin films of different morphology and composition (ranging from x=0-0.4) were characterized by surface analytical techniques as well as electrochemical impedance spectroscopy (EIS). EIS allows to precisely control the atmospheric conditions such as gas type and mixture or temperature and humidity using a respective experimental setup described in the methods section of this manuscript. The presented work focuses on the influence of grain boundaries and the surface, as they play an important role for thin film transport processes. Electrochemical impedance spectroscopy allows to deduce transport properties of the thin films under investigation and compare those to respective models. At moderate and very low temperatures down to room temperature water influences the conductivities determined during the experiments. In the respective literature which is going to be reviewed in the theoretical section of this work an ongoing discussion on the influence of water vapor in the surrounding atmosphere (humidity) during impedance measurements is revealed. The experimental results in this work are described in good agreement by a model combining thermodynamic adsorption models with the theory of percolating networks. These results reveal valuable information to the ongoing discussions in literature.
Keywords: ceria; defect chemistry; conductivity; ddc:540